Respuesta del cultivo de Alelí (Matthiola Incana) a la aplicación de tres láminas de riego bajo invernadero en el campus Salache, cantón Latacunga, provincia Cotopaxi 2023 - Taco Guamán, Roberto Alexander (2023)
Due to the current and growing floricultural activity in the province of Cotopaxi, the lack of technologies and the low availability of water in some areas, it is essential to evaluate the response of four varieties of alelí (Matthiola incana) to the application of three irrigation sheets at the Salache campus of the Technical University of Cotopaxi, under greenhouse conditions using an experimental methodology, the agronomic behavior of the alelí was carried out under three irrigation sheets, at 100% crop evapotranspiration (ETc) or control and two deficit sheets at 90% and 80% of the crop evapotranspiration (ETc), with a high-frequency localized irrigation system (drip tape), in the fuchsia, white, yellow and aprico varieties. The experimental design was completely randomized blocks (DBCA), with 12 treatments and three repetitions, with a total of 36 experimental units. The results allowed us to identify that the four variables evaluated did not show a large significant difference between the twelve treatments; That is, in this case the Alelí varieties used are not influenced by the irrigation sheets.